(untitled) (Slavic Studies, 2024)
This article concerns the reception of Olga Tokarchuk’s literary works, as she is one of the most outstanding writers of the present day, not only in Polish literature. This concerns theperspective of a translator working in a different environment which is also important, because it could differ both from the country of origin and from that of other countries where Olga Tokarchuk might be more popular. The analysis of her five works translated into Macedonian hepled us derive the dominant featuresthat determine her writing style and which we try to explain through the prism of her own words, expressed mainly in the essay entitled “Tender Narrator”.